PENGARUH LAYANAN INFORMASI TERHADAP MANAJEMEN STRES SISWA DI KEHIDUPAN ASRAMA (BOARDING SCHOOL) KELAS X SMK KEHUTANAN NEGERI PEKANBARU TAHUN AJARAN 2014/2015 - Sartika Sari Zaid Sari Zaid; Zulfan Saam Zulfan Saam; Raja Arlizon Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The threatening conditions often cause students feel depressed. Therefore, it is important for the students to have skills in order to manage their stress in the form of Stress Management. The objective this research are (1) to describe students’ Stress Management before Information Services were applied, (2) to identify the process in giving Information Services to the students’ Management Stress, (3) to identify the description of students’ Stress Management after Information Services were applied, (4) to identify the differences of students’ Stress Management before and after Information Services are were applied, (5) to identify the influences of Information Services to the students’ Stress Management. This research used the pre-experimental method with one group pretest-posttest design. The subject of this research is class X of SMK Kehutanan Negeri Pekanbaru, that consist of 100 students. The sample was determined by using saturated sample. In order to distinguish students’ Management Stress before and after Information Services given, "t" test is applied and thitung obtaining a greater score ttabel than the score at the level of 5% (11,29>1,960). Ho was rejected and Ha was accepted which meant in this research differences before and after the implementation of Information Service to increase students’ Stress Management. The result of the moment product testing r=0,34 and the determination coefficient r2=0,11. Based on the result of conducted research, it can be concluded that after the implementation of Information Service, the students’ Stress Management in Boarding School of class X SMK Kehutanan Negeri Pekanbaru has increased 11%.Key Words: Information Service, Stress Management, Boarding School.